(untitled) - Ellwood, David T (New York, 1988)
Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Family policy -- United States; Poor -- Government policy -- United States; Public welfare -- United States; Social security -- United States; Chính sách gia đình -- Hoa Kỳ; Nghèo -- Chính sách của chính phủ -- Hoa Kỳ; Phúc lợi công cộng -- Hoa Kỳ